Polycrystalline and Single‐Crystal Cu Electrodes: Influence of Experimental Conditions on the Electrochemical Properties in Alkaline Media. Issue 67 (7th November 2018) - Engstfeld, Albert K.; Maagaard, Thomas; Horch, Sebastian; Chorkendorff, Ib; Stephens, Ifan E. L.
Abstract: Single and polycrystalline Cu electrodes serve as model systems for the study of the electroreduction of CO2, CO and nitrate, or for corrosion studies; even so, there are very few reports combining electrochemical measurements with structural characterization. Herein both the electrochemical properties of polycrystalline Cu and single crystal Cu(1 0 0) electrodes in alkaline solutions (0.1 m KOH and 0.1 m NaOH) are investigated. It is demonstrated that the pre‐treatment of the electrodes plays a crucial role in determining their electrochemical properties. Scanning tunneling microscopy, X‐ray photoelectron spectroscopy and cyclic voltammetry are performed on Cu(1 0 0) electrodes prepared under UHV conditions; it is shown that the electrochemical properties of these atomically well‐defined electrodes are distinct from electrodes prepared by other methods. Also highlighted is the significant role of residual oxygen and electrolyte convection in influencing the electrochemical properties. Abstract : Pre‐treatment matters : The electrochemical properties of Cu(1 0 0) single‐crystal electrodes prepared with different pre‐treatments were investigated by cyclic voltammetry in alkaline media. Since the atomically flat Cu(1 0 0) electrodes prepared under ultrahigh vacuum (UHV) conditions show a distinct electrochemical response compared to those prepared under laboratory conditions, the CV recorded on Cu(1 0 0)‐UHV electrodes provides a benchmark for further studies on Cu(1 0 0) single crystals.